(3Jehjd h eDSSGJ eGdjI (B/s - (3HTjQ GdeZQHj, eMeO GdaGJM eMehOs ((3GdbGgQI(B: s (3GdTQcI GdYQHjI GdeJMOI ddJShjb h GdJhQjOGJ(B, s, 2011)
(3WHjYI h CgjI h CfhGY GdeUGQa GdJLGQjI , GdHhQUGJ h eDSSGJ GdJehjd GdOhdjI h GdGbdjejI , GdJehjd h Gdgjcd GdeGdj , JcdaI GdJehjd h bQGQGJ Gdgjcd GdeGdj ddefTCI h Jehjd GdeTQhY , Jbjje GdGSJKeGQ h GdGfaGb GdGSJKeGQj , GdNWQh GdJCejfs
Keywords: (3GdHfhc GdJLGQjIs; (3GdHhQUGJs; (3GdJCejf(B- (3eNGWQs; (3GdJehjds